The clinical effectiveness and cost effectiveness of lamotrigine for people with borderline personality disorder: a randomized, placebo-controlled trial - Crawford, Mike J.; Sanatinia, Rahil; Barrett, Barbara; Cunningham, Gillian; Dale, Oliver; Ganguli, Poushali; Lawrence-Smith, Geoff; Leeson, Verity; Lemonsky, Fenella; Lykomitrou, Georgia; Montgomery, Alan A.; Morriss, Richard K.; et al. (American Psychiatric Publishing, 2018)
Objectives: To examine whether lamotrigine is a clinically effective and cost-effective treatment for people with borderline personality disorder.